2018
DOI: 10.11114/aef.v5i6.3690
|View full text |Cite
|
Sign up to set email alerts
|

Structural Breaks and Volatility Persistence of Stock Returns: Evidence from the US and UK Equity Markets

Abstract: This paper quantitatively investigates the effects of structural breaks on stock return volatility persistence by using the US and UK stock market index return data. Applying two kinds of representative univariate GARCH models of standard GARCH and EGARCH models, we derive the following interesting findings. (1) First, we find that for both the US and UK stock market returns, the volatility persistence parameter values of standard GARCH models decrease when structural breaks are taken into account. (2) Second,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…As a result, they suffer from slow information flow and sluggish absorption of news into the market prices leading to long-term adjustments. Notably, the extremely high volatility persistence levels of close to 1 in China and Russia may suggest significant evidence of structural breaks (Kasman 2009;Tsuji 2018).…”
Section: Variance Equation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, they suffer from slow information flow and sluggish absorption of news into the market prices leading to long-term adjustments. Notably, the extremely high volatility persistence levels of close to 1 in China and Russia may suggest significant evidence of structural breaks (Kasman 2009;Tsuji 2018).…”
Section: Variance Equation Resultsmentioning
confidence: 99%
“…On the same market, Goldman and Shen (2018), over the period 2002-2017, reported volatility persistence, asymmetry and a positive risk premium. Tsuji (2018) found that standard GARCH and EGARCH models' volatility persistence parameter values decreased when structural breaks were considered. Thus, failure to consider structural breaks may result in an overestimation of volatility persistence of international stock returns.…”
Section: Literature Reviewmentioning
confidence: 96%
“…This paper quantitatively examined the effects of structural breaks in stock returns on their volatility persistence by using the return data of S&P 500 in the US and TOPIX in Japan. In the fields of business, economics, and finance, it is well-known that GARCH models are highly beneficial and important as Bollerslev (1986), Nelson (1991), Engle and Kroner (1995), Tsuji (2016bTsuji ( , 2018d, and numerous other studies suggested. Based on this, applying the diagonal BEKK-MGARCH models with and without structural break dummies, we revealed the following interesting findings.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, by applying a new DCC-MEGARCH model, Tsuji (2018c) explored return and volatility transmission between international oil equities and WTI crude oil futures, in which structural break analyses were also conducted for robustness checks. Furthermore, Tsuji (2018aTsuji ( , 2018b also investigated the linkages between stock return structural breaks and their volatility persistence, although the examinations were by univariate analyses.…”
Section: Related Literature Reviewmentioning
confidence: 99%
“…In business and finance literature, structural breaks in time-series stock returns become highly important, and recently, the volatility spillover in international stock markets is also being very important research topic (e.g., Diebold and Yilmaz, 2012;Ewing and Malik, 2016;Tsuji, 2018a;Tsuji, 2018b). Then how are stock return volatility spillovers affected by their structural breaks?…”
Section: Introductionmentioning
confidence: 99%